Introduction to criminology: theories, methods, and criminal behavior - Hagan, Frank E. (Sage Publications, 2011)
Introduction -- Research methods in criminology -- General characteristics of crime and criminals -- Early and classical criminological theories -- Positivist theories : biological and psychological -- Sociological mainstream theories -- Sociological critical theories and integrated theories -- Violent crime -- Property crime : occasional, conventional and professional -- White collar crime: occupational and corporate -- Political crime -- Organized crime -- Public-order crime -- Computer crime -- Epilogue : the future of crime